SEG Applied Research Workshop: Geophysical challenges in southeast Asia exploration - REILLY, JOSEPH M (Society of Exploration Geophysicists, 2008)
The 2008 SEG Applied Research Workshop, in Kuala Lumpur, Malaysia on 7–10 April 2008, was the fi rst such event to focus on regional challenges rather than on a specifi c technical topic. Th is is a premier example of how SEG is exploring for new ways to reach out and encourage more interaction with its global membership base. Th e workshop attracted 64 attendees, with regional representation from Malaysia, Th ailand, Indonesia, and India; attendees from outside the region represented North America, Europe, and Australia. Th e participants covered the full spectrum of business interests: international oil companies, national oil companies, independent oil companies, research institutes, and geophysical service providers. Th e workshop was sponsored by Hess Corporation, ExxonMobil, and National GeoConsultant of Indonesia.